The formation of the state and of communal lands (ejidos) in a part of la huasteca potosina, 1920-1945 (Tzintzun, Revista de Estudios Históricos, 2016)
he main focus of this paper is the process of the formation of communallands in a selected area as part of the formation and construction of the postrevolutionarystate. In this sense, it seeks to retrieve a signiicant part of thelocal history, the speeches and examples of peasant leadership of the municipalityof Tanlajas, encompassing them in a major historical context. Furthermore,the present contribution aims at combining oral history and thedocumented history available in the Historic Archives of the National AgrarianOice of San Luís Potosí with ield evidence, especially by elaboratingoriginal cartography on forms of land ownership until 1920 in a gis format,in order to study the processes of the agrarian reform. he use of the gis toolshas allowed a novel insight into the interpretation of the maps available in theagrarian records, and it has led to a better present-day geographic localizationof the historical forms of land ownership.
Keywords: post-revolutionary state; communal lands (ejidos); huasteca; Tének; geography